The Strategy of Resistancy and the 'Cultural Hegemony of Transparent Discourse in English-language Translation' (Stamford Journal of English, 2013)
The paper hinges basically on Venutis notion of resistancy, a strategy which "seeks to free the reader of translation, as well as the translator, from the cultural constraints that threaten to overpower and domesticate the foreign text, annihilating its foreignness" (Venuti 305). The orientation of modernist translation towards favouring the domestic over the foreign, the dynamic over the semantic, and the reader-oriented over the author-oriented are highly questioned and argued against in this paper. The stand taken by this paper, however, is not to be mistaken as one that favours literalist translation. The paper seeks to argue in favour of the strategy of resistancy as a new anti-modernist-translation notion in the field of translation theory and practice. This strategy opposes the cultural hegemony of narcissist strategies that promote the obliteration of the uniqueness of the foreign text when translated into the hegemonial Anglo-American English. The paper also attempts to revisit the existing and dominant notions related to the ethics of responsibility and normality in translation as one way to correct the mainstream translational practices and theorising. The paper concludes its statements with further reflections on Venuti's terminological choices, and with some practical mediating suggestions for the promotion of Venuti's notion of resistancy and the advocacy of mutual-respect ethics between cultures. Stamford Journal of English; Volume 6; Page 219-229 DOI: http://dx.doi.org/10.3329/sje.v6i0.13915